Akibat Hukum Transaksi Jual Beli Dalam Kaitannya Dengan Validasi Pajak Daerah Oleh Badan Pengelolaan Keuangan Dan Aset Daerah Kabupaten Pelalawan - Suhendar, Suhendar; Yuslim, Yuslim; Syofiarti, Syofiarti (UNES Law Review, 2023)
Pelalawan district often finds that the price of buying and selling transactions for land and buildings that occur during the transfer of rights does not match the actual transaction price, this creates an imbalance that can be detrimental to taxpayers and local government agencies themselves, such as buying and selling transactions that occur far away. below the actual market price used as the basis for NPOP in calculating BPHTB. If this is done intentionally, then the action can be categorized as tax evasion. The approach used in this research is an empirical juridical approach. The data used in this research are secondary data and primary data. All data and materials obtained from research results are compiled and analyzed qualitatively, and presented in qualitative descriptive form. From the research results, it can be explained that: First, the implementation of buying and selling transactions in relation to regional tax validation by the Regional Financial and Asset Management Agency of Pelalawan Regency has no authority to validate price determination that exceeds the price of buying and selling transactions that have been made by the parties and there are no regulations. which requires validation of pricing determinations. The Pelalawan Regency Regional Financial and Asset Management Agency only has the authority to check the payment of tax deposits in the transfer of rights to land and buildings, as well as ensuring whether the tax deposits have been paid by the parties in the sale and purchase transaction for the transfer of rights to land and buildings. Second, the legal consequences of buying and selling transactions in relation to the validation of regional taxes by the Regional Financial and Asset Management Agency of Pelalawan Regency, where the Notary as PPAT must wait for the day, date and time to be included when the parties appear. The inclusion of the day, date, month, year and time when the parties appear will only be included at the beginning of the Sale and Purchase Deed after the validation process is complete. The notary as PPAT for this action violates the UUJN, because there is an element of falsification in that the inclusion of the day, date, month, year and time when appearing does not correspond to the reality that occurred when the parties appeared. The action of the Notary as PPAT to include false information in the authentic deed results in the deed becoming null and void. A notary as a PPAT can be punished for false information stated in the deed.